Properties of elastomeric calcium phosphate cement–chitosan composites - Takagi, Shozo; Chow, Laurence C; Hirayama, Satoshi; Eichmiller, Frederick C (Dental materials, 2003)
Objective. Self-hardening calcium phosphate cements (CPC) have been shown to be efficacious in a number of clinical applications. For some applications it is desirable to have CPC in a non-rigid resorbable elastomeric matrix. In the present study, chitosan was evaluated as the matrix for preparing CPC-chitosan composites. Methods. Cement specimens were prepared by mixing CPC powder (an equimolar mixture of tetracalcium phosphate and dicalcium phosphate anhydrous) with a chitosan solution at a powder/liquid ratio of 2–2.5. The setting time was measured by a Gilmore needle method. A standard three-point flexural test was used to fracture the specimens at a crosshead speed of 0.5 mm/min. Powder X-ray diffraction analysis was used to determine the conversion of the CPC to hydroxyapatite. Results. The CPC–chitosan composites were more stable in water than conventional CPC. They did not disintegrate even when placed in water immediately after mixing. The CPC–chitosan paste hardened within 10 min in all cases. The 1 d mean flexural modulus (GPa) for the control CPC was 5.3 (0.3) (mean (standard deviation); n=5), and that for CPC–chitosan composites were between 2.7 (0.3) and 4.7 (0.3). The 1 d mean flexural strength (MPa) for the control was 16.6 (1.9), and that for the CPC–chitosan ranged from 4.5 (0.5) and 12.0 (1.0) ( n=5). Chitosan did not interfere the conversion of CPC components to hydroxyapatite. Significance. This study demonstrates that CPC–chitosan composites are stable in a wet environment and have acceptable mechanical strengths for clinical applications.